The impact of river pollution on health disorders - Singh, Rajeev Pratap (Universitas Nahdlatul Ulama Surabaya, 2024)
River pollution in Indonesia is a serious problem that has a wide impact on public health. Rivers, as the main water source for many communities, are often polluted by human activities, such as industrial waste, domestic waste, and agriculture. Method: This study is a literature review. The database used in searching for this article is Google Scholar, 5 journals were obtained which were then analyzed for topic suitability, discussed based on criteria from variable similarities and differences. time span 2018-2021. Results: Diseases related to water pollution in communities living around polluted rivers often experience various health problems. Some common diseases include skin irritation such as itching and dermatitis, which are caused by direct contact with polluted river water. suffering from diarrhea is caused by consuming contaminated water or food. Diarrhea is one of the most common diseases, especially among children and cases of dysentery are also found. Conclusion: Diseases related to poor water quality include skin irritation such as dermatitis, which are caused by direct contact with polluted river water. suffering from diarrhea is caused by consuming contaminated water or food and cases of dysentery are also found.